2006
DOI: 10.1186/1710-1492-2-3-109
|View full text |Cite
|
Sign up to set email alerts
|

The Difficult-to-Control Asthmatic: A Systematic Approach

Abstract: With the judicious use of inhaled corticosteroids, β2 agonists, and leukotriene modifiers, most patients with asthma are easily controlled and managed. However, approximately 5% of asthmatics do not respond to standard therapy and are classified as "difficult to control." [1] Typically, these are patients who complain of symptoms interfering with daily living despite long-term treatment with inhaled corticosteroids in doses up to 2,000 μg daily. Many factors can contribute to poor response to conventional ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…Nevertheless, further research is urgently needed to enhance prevention and improve treatment of allergic diseases because current therapies are of limited efficacy due to issues such as poor compliance, corticosteroid resistance, and ineffective control of exacerbating factors, including air pollution. 67 Key messages…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, further research is urgently needed to enhance prevention and improve treatment of allergic diseases because current therapies are of limited efficacy due to issues such as poor compliance, corticosteroid resistance, and ineffective control of exacerbating factors, including air pollution. 67 Key messages…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VCD was 22% for persons requiring repeated emergency room visits due to sudden-onset shortness of breath [38]. The condition was observed in about 10% of patients seeking evaluation of asthma unresponsive to aggressive therapy [39,40]. VCD was mistaken for refractory asthma [33].…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled severe asthma accounts for ~15% of all asthma patients but is associated with a higher morbidity and mortality as well as an important impact on health care costs and the consumption of resources. 15 The AsmaCost study 16 based on data of a prospective cohort of 627 patients throughout Spain with asthma diagnosed according to the guidelines of the Global Initiative for Asthma (GINA) 17 and the adapted Spanish criteria (Guía Española de Manejo del Asma [GEMA]) 9 and followed up for 12 months revealed that the total societal cost for asthma was 1,726€ per patient annually (1,533€ to the National Health Service), with higher costs for patients older than 65 years and for those with a more severe disease (2,635€ for severe asthma). Based on these findings, the total annual cost of asthma in Spain was estimated to be 1,480 million euros.…”
Section: Difficult-to-control Asthmamentioning
confidence: 99%
“…On the other hand, 70% of total costs were attributed to the poor control of the disease, which further reinforces the need to achieve clinical stability of the patients as it has been repeatedly emphasized in clinical practice guidelines. 9 , 17…”
Section: Difficult-to-control Asthmamentioning
confidence: 99%
See 1 more Smart Citation